Cd and Pb Levels in the Soft Tissue of Black Mussel (Mytilus galloprovincialis) Collected from Marmara Sea, Pendik District Coastal Area, Istanbul, Turkey - (:unkn) unknown (ZOOLOGICAL SOC PAKISTAN, 2016)
The aim of this study was to determe cadmium and lead concentrations in the whole soft tissue of the black mussels (Mytilus galloprovincialis Lamarck, 1819) (n=60) caught from Pendik district coasts of Istanbul, Turkey. According to legal standards of Turkish Food Codex (TFC) and United Nations Environment Programme (UNEP) standards the level of Cd was low white that of Pb was high. The highest Pb concentration found in the whole soft tissue of mussels at S4 was 8.66 (February), 6.64 (January), 4.72 ppm Pb (July 2011) whereas in S5 it is 8.66 (November), 8.14 (February), 6.64 (October), 4.57 ppm (June 2012).
Keywords: Cadmium; lead; heavy metal pollution; Mytilus galloprovincialis; black mussel; HEAVY-METAL ACCUMULATION; SURFACE SEDIMENTS; OXIDATIVE STRESS; TRACE-METALS; WATER; POLLUTION; BOSPORUS; RISK; LEAD